Sars-CoV-2 (COVID-19) inactivation capability of copper-coated touch surface fabricated by cold-spray technology. (August 2020) - Hutasoit, Novana; Kennedy, Byron; Hamilton, Stephanie; Luttick, Angela; Rahman Rashid, Rizwan Abdul; Palanisamy, Suresh
Abstract: In this work, cold-spray technique was employed for rapid coating of copper on in-use steel parts. The primary intention was to alleviate the tendency of SARS-CoV-2 (COVID-19) virus to linger longer on touch surfaces that attract high-to-medium volume human contact, such as the push plates used in publicly accessed buildings and hospitals. The viricidal activity test revealed that 96% of the virus was inactivated within 2-hrs, which was substantially shorter than the time required for stainless steel to inactivate the virus to the same level. Moreover, it was found that the copper-coated samples significantly reduces the lifetime of COVID-19 virus to less than 5-hrs. The capability of the cold-spray technique to generate antiviral copper coating on the existing touch surface eliminates the need for replacing the entire touch surface application with copper material. Furthermore, with a short manufacturing time to produce coatings, the re-deployment of copper-coated parts can be accomplished in minutes, thereby resulting in significant cost savings. This work showcases the capability of cold-spray as a potential copper-coating solution for different in-use parts and components that can act as sources for the spread of the virus.